Decentralized environmental regulations and plant‐level productivity. (21st March 2019) - Ghosal, Vivek; Stephan, Andreas; Weiss, Jan F.
Abstract: Using the framework provided by the Porter hypothesis, we study the impact of environmental regulations and enforcement policies on plant‐level green total factor productivity (TFP) growth and its components related to efficiency change and technical change. The detailed microdata we use are from Sweden and for the pulp and paper industry. This industry is the source of significant amounts of water and air pollution and is one of the most heavily environmentally regulated manufacturing industries. Sweden has a unique decentralized regulatory structure where the manufacturing plants have to comply with plant‐specific regulatory standards stipulated at the national level, as well as decentralized local supervision and enforcement. Our empirical results point to beneficial impacts of the environmental policies on plants' green TFP growth and sustainable production practices. We also find that political economy considerations are important, as the presence of the Green Party and aspects like plant size (with corresponding local and regional economic effects) matter in enforcement of the standards.